2005
DOI: 10.1128/jvi.79.9.5850-5856.2005
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Functional Domains in Kaposica, the Complement Control Protein Homolog of Kaposi's Sarcoma-Associated Herpesvirus (Human Herpesvirus 8)

Abstract: Recently it has been shown that kaposica, an immune evasion protein of Kaposi's sarcoma-associated herpesvirus, inactivates complement by acting on C3-convertases by accelerating their decay as well as by acting as a cofactor in factor I-mediated inactivation of their subunits C3b and C4b. Here, we have mapped the functional domains of kaposica. We show that SCRs 1 and 2 (SCRs 1-2) and 1-4 are essential for the classical and alternative pathway C3-convertase decay-accelerating activity (DAA), respectively, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 33 publications
(37 reference statements)
4
34
0
Order By: Relevance
“…The point mutants Arg20Gln/Arg33Gln/Arg35Gln and Lys64Gln/Lys65Gln/Lys88Gln did not bind to heparin, which localizes the heparin binding site to CCP1, stretching in to CCP2. Heparin binding to CCP1 was also observed in (Mullick et al, 2005). Single point mutations were not as defective in heparin binding as the corresponding triple mutant, indicating that the interaction is dependent on several bonds between the heparin molecule and different amino acids in KCP, which agrees well with what has been observed for most other heparin-protein interactions (Capila and Linhardt, 2002).…”
Section: Discussionsupporting
confidence: 84%
“…The point mutants Arg20Gln/Arg33Gln/Arg35Gln and Lys64Gln/Lys65Gln/Lys88Gln did not bind to heparin, which localizes the heparin binding site to CCP1, stretching in to CCP2. Heparin binding to CCP1 was also observed in (Mullick et al, 2005). Single point mutations were not as defective in heparin binding as the corresponding triple mutant, indicating that the interaction is dependent on several bonds between the heparin molecule and different amino acids in KCP, which agrees well with what has been observed for most other heparin-protein interactions (Capila and Linhardt, 2002).…”
Section: Discussionsupporting
confidence: 84%
“…Alternatively, the dissociation of C2a by the domain 1 could be a result of a conformational change in the vWFA domain. Previous observations on domain mapping of other viral complement regulators have shown that domains 1-2 are the minimum domains important for CP DAA in Kaposica (48) and soluble complement control protein homolog of herpesvirus saimiri (49). It is therefore possible that like VCP, domain 1 in these proteins too contributes to dissociation of C2a from the CP C3 convertase and other domains play a supportive role in binding to C4b.…”
Section: Vcp Domains Critical For Daasmentioning
confidence: 99%
“…A similar mechanism could also be operative for the interaction of VCP with C4b and factor I. Because domain requirements for ligand binding and CFAs in viral (34,48,49,54) and human complement regulators (55)(56)(57)(58)(59)(60)(61)(62) are conserved, it could be inferred that the recognition sites for C3b/C4b and factor I are spatially conserved in both human and viral complement regulators, and that they employ a common mechanism to inactivate C3b and C4b.…”
Section: Vcp Domains Critical For Factor I Cfasmentioning
confidence: 99%
“…Armed with this information on DAF, we then analyzed the extent of conservation of residues in DAF and in other C3 convertase regulators determined by mutagenesis to be important, either for cofactor activity or for DAA (12,18,21,22,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). Whereas we found an absence of strict conservation of residues which distinguish the two functions, by focusing alignment on the sequence flanking the CCP2 and -3 junction where DAF function resides, we identified differences between those regulators that 1) mediate DAA and 2) mediate cofactor activity.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table 4, this analysis yielded DAF homologs from a variety of species as well as ϳ10 other proteins. Among known proteins having DAA are CR1 (site 1; CCP1 to -3) (21), Kaposica (22), mouse Crry (23), and the recently reported but only partially character- important residues labeled (12, 18, 21, 22, 25-41). DAF-2, CCP2 of DAF; CR1-1, CCP1 of CR1, etc.…”
Section: Correlation Of the Daf Active Site Residues With Correspondimentioning
confidence: 99%